Effect analysis of power density distribution & temperature dependent thermo-physical properties along MSR fuel channels applying neutronic and thermal hydraulic approach - Mohammad Khan; Nayeem bin Zahid; Saad Islam; Ali Mahdi (Nuclear Engineering and Technology, 2025)
One of the potential Generation IV reactors is MSR for its several advantages including actinides burning, production of hydrogen, and fissile breeding. The distinct feature that sets the MSR apart from other reactors is the mixing of fissile material with molten halide salt, playing the vital role of both the heat transferring coolant and heat generating fuel. This dual-function fluid circulates through a graphite moderator matrix, forming a complex system that poses significant computational challenges, particularly for coupled neutronic-thermal hydraulic simulations. To address these challenges, simplified assumptions—such as sinusoidal power distributions and temperature-independent material properties—are often employed. In this study, a single MSR fuel channel is analysed under varying power density distribution assumptions, with and without incorporating the temperature dependence of material properties, using a decoupled neutronic and thermal-hydraulic modelling approach. To determine the power distribution via neutron flux profiles, a probabilistic approach was employed using the Monte Carlo particle transport code OpenMC. For the thermal-hydraulic analysis, the Reynolds-Averaged Navier–Stokes (RANS) equations with the k–ε turbulence model were utilized and implemented using the state-of-the-art commercial computational fluid dynamics software, ANSYS Fluent. The results were compared to analytical solutions available in the literature, as well as to results obtained through fully coupled neutronic-thermal hydraulic simulations. The study revealed that assuming uniform heat generation in the MSR channel significantly affects the temperature profile along the channel. It also indicated that axial variations in heat generation are the most influential factor affecting the temperature distribution. Additionally, other flow properties such as velocity profiles and Nusselt number distributions were examined.